Reasserting the principle of legality in the wake of the COVID-19 pandemic - Kos, Marjan (Zbornik znanstvenih razprav (Pravna fakulteta. 1991), 2022)
In a response to the COVID-19 pandemic, the Slovenian Government adopted numerous measures that were substantively similar to those, adopted in other states. The scope and intensity of those measures significantly affected the principle of the separation of powers and the protection of human rights. In this context, the Constitutional Court of the Republic of Slovenia adopted Decision U-I-79/21, which marked the contours for the review of legality and constitutionality of the Governmental measures in subsequent cases. The key message of the Decision was the demand for the strict observance of the principle of legality when adopting measures to prevent the spread of COVID-19, which interfere with human rights. This article explains the context of the Decision and presents key arguments from the Decision and the concurring and dissenting opinions as well as the response of the expert community.
Keywords: COVID-19; človekove pravice; delitev oblasti; pandemije; sodna praksa; ustavna sodišča; varnostni ukrepi; Zakon o nalezljivih boleznih